ESTIMATION OF THE PERSPECTIVE AIRSPACE USE PLANNING SYSTEM FOR AIRCRAFT OF THE STATE AVIATION IN MOSCOW CFPU - I. A. Chekhov (Научный вестник МГТУ ГА)
The article presents the results of calculation and a comparative estimation of the perspective and operating airspace use planning system for aircraft of the state aviation in Moscow CFPU on the basis of statistical data for 2010-2014. In the article the peculiarities of the existing system of planning of air space use are emphasized. According to the calculations it has a three to four-fold reserve under ideal conditions of its functioning and may accept plenty of applications for airspace use for some time. However, its detailed consideration shows that it is at the limit of state aviation flights capabilities. It can be noted that the number of state aviation flights has not reached its peak yet and in 2014 it even decreased by 8 % compared to 2013.